Yami ni kizamu hikari Ajia no mokuhanga undō : 1930s-2010s = Woodcut movements in Asia : blaze carved in darkness - Kuroda, Raiji; Igarashi, Rina; Doloricon, Leonilo O.; Tapang, Lisa Ito (Fukuoka Asian Art Museum, 2018)
Focuses on woodcuts (woodcut prints) in Asia from the 1930s to recent years, and seeks to rearticulate the history of modern and contemporary Asian art through movements using woodcut as media to convey information and messages to the masses.